ID: 100: A SYSTEMATIC REVIEW AND META-ANALYSIS OF THE RELATIVE EFFICACY AND SAFETY OF TREATMENT REGIMENS FOR HIV-ASSOCIATED CEREBRAL TOXOPLASMOSIS. Issue 4 (22nd March 2016) - Thota, P; Pasupuleti, V; Pellegrino, D; Benites-Zapata, VA; Deshpande, A; Vidal, JE; Hernandez, AV
Abstract : Aim: The objective of this study was to perform a systematic review and meta-analysis of the literature to evaluate efficacy and safety of therapies for cerebral toxoplasmosis in HIV-infected adults. Pyrimethamine plus sulfadiazine (P-S) combination is considered the mainstay therapy for cerebral toxoplasmosis and pyrimethamine plus clindamycin (P-C) is the most common alternative treatment. Although, trimethoprim-sulfamethoxazole (TMP-SMX) has potential advantages, its use is infrequent. Methods: Design: Systematic review and meta-analysis. We searched PubMed and 4 other databases to identify randomized controlled trials (RCTs) and cohort studies. Two independent reviewers searched and identified studies and extracted data. Risk ratios (RRs) were pooled across studies using random-effects models. Results: Nine studies were included (5 RCTs, 3 retrospective cohorts, 1 prospective cohort). In comparison to P-S, treatment with P-C or TMP-SMX had similar partial or complete clinical response (P-C: RR 0.87, 95%CI 0.70–1.08; TMP-SMX: RR 0.97, 95%CI 0.78–1.21), radiological response (P-C: RR 0.92, 95%CI 0.82–1.03), skin rash (P-C: RR 0.81, 95%CI 0.56–1.17; TMP-SMX: RR 0.17, 95%CI 0.02–1.29), gastrointestinal impairment (P-C: RR 5.16, 95%CI 0.66–40.11), and drug discontinuation due to adverse events (P-C: RR 0.32, 95%CI 0.07–1.47). Liver impairment was more frequent with P-S than P-C (P-C vs P-S: RR 0.48, 95% CI 0.24–0.97). Conclusions: The current evidence fails to identify one superior regimen in terms of relative efficacy or safety for the treatment of HIV-associated cerebral toxoplasmosis. Use of TMP-SMX as preferred treatment may be consistent with the available evidence and other real world considerations. Larger comparative studies are needed.